Anti-cancer immune effect of human colorectal cancer neoantigen peptide based on MHC class I molecular affinity screening - Zhang, Siyu; Huang, Changxin; Li, Yongqiang; Li, Zhaoyang; Zhu, Ying; Yang, Lili; Hu, Haokun; Sun, Quan; Liu, Mengmeng; Cao, Songqiang (Frontiers in Immunology, 2024)
Recently, tumor antigen peptide vaccines have demonstrated remarkable efficacy, safety, and reliability. However, the cumbersome screening process for immunopotent antigenic peptides has hindered their widespread application.Whole exon sequencing was performed on patient-derived colon cancer cells to predict 9aa neoantigen peptides for in vitro simulation of endogenous antigen presentation by antigen-presenting cells (dendritic cell) to CD8+ T cells, thereby activating the CD8+ immune response to the antigen. The immunological effects of each neoantigen were investigated using flow cytometry and ELISpot assays to elucidate the relationship between neoantigen immunogenicity and MHC molecular affinity, thereby allowing the establishment of a simplified screening model based on this relationship. The rapid screening of immunoeffective neoantigens based on this model holds significant potential for the clinical application of individualized tumor antigen peptides.